2017
DOI: 10.1177/0891988717720298
|View full text |Cite
|
Sign up to set email alerts
|

Modified Pfeffer Questionnaire for Functional Assessment in Parkinson Disease

Abstract: 3.5 is proposed as the cutoff point to define functional impairment in patients with PD by mPQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…For this approach, we used the FAQ, which was divided into two subscores, the FAQ C and the FAQ M , to differentiate cognitive-and motor-driven aspects of ADL function. Contrary to the approach by Almeida et al (2017), we chose to include all FAQ items in our analyses and separate the cognitive and motor contributions using a data-driven analysis. Their approach was theory-driven by validating their modified FAQ and its cut-off using a separate, informant-based questionnaire assessing ADL impairment changes over 2 years, instead of using motor and cognitive scales as validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this approach, we used the FAQ, which was divided into two subscores, the FAQ C and the FAQ M , to differentiate cognitive-and motor-driven aspects of ADL function. Contrary to the approach by Almeida et al (2017), we chose to include all FAQ items in our analyses and separate the cognitive and motor contributions using a data-driven analysis. Their approach was theory-driven by validating their modified FAQ and its cut-off using a separate, informant-based questionnaire assessing ADL impairment changes over 2 years, instead of using motor and cognitive scales as validation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Almeida et al . () modified the Pfeffer Functional Activities Questionnaire (FAQ), a validated assessment for ADL impairment, to exclude some questions which might pertain to motor skills. Their data confirmed that the FAQ is a valid measure for functional impairment in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborando com esses dados, dois estudos brasileiros sugeriram que o questionário da pílula é menos sensível do que outros instrumentos para detectar comprometimento funcional 15,33 . Estudos prévios avaliando pacientes brasileiros com DDP utilizaram alguns instrumentos para avaliar habilidades funcionais, incluindo o questionário de atividades funcionais de Pfeffer, Avaliação de Incapacidade em Demência (DAD), Questionário de Informante sobre Declínio Cognitivo em Idosos (IQCODE), Pill Questionnaire, teste de telefone e Avaliação Direta da Capacidade Funcional (DAFA) 15,[33][34][35][36][37] . Dois estudos avaliaram a precisão do Pfeffer para detectar comprometimento funcional em pacientes com DP 33,37 .…”
Section: Caraterísticas Clínicas Principaisunclassified
“…Estudos prévios avaliando pacientes brasileiros com DDP utilizaram alguns instrumentos para avaliar habilidades funcionais, incluindo o questionário de atividades funcionais de Pfeffer, Avaliação de Incapacidade em Demência (DAD), Questionário de Informante sobre Declínio Cognitivo em Idosos (IQCODE), Pill Questionnaire, teste de telefone e Avaliação Direta da Capacidade Funcional (DAFA) 15,[33][34][35][36][37] . Dois estudos avaliaram a precisão do Pfeffer para detectar comprometimento funcional em pacientes com DP 33,37 . Oliveira et al propôs que pontuação maior que dois pontos na escala de Pfeffer tinha uma sensibilidade de 23% e uma especificidade de 74% para predizer desempenho anormal em um teste cognitivo global 33 .…”
Section: Caraterísticas Clínicas Principaisunclassified
See 1 more Smart Citation